Faculty Perspectives of Academic Integrity During COVID-19: A Mixed Methods Study of Four Canadian Universities - Eaton, Sarah Elaine; Stoesz, Brenda M.; Crossman, Katherine; Garwood, Kim; McKenzie, Amanda (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2022)
Faculty members are crucial partners in promoting academic integrity at Canadian universities, but their needs related to academic integrity are neither well documented nor understood. To address this gap, we developed a mixed methods survey to gather faculty perceptions of facilitators and barriers to using the existing academic integrity procedures, policies, resources, and supports required to promote academic integrity. In this article, we report the data collected from 330 participants at four Canadian universities. Responses pointed to the importance of individual factors, such as duty to promote academic integrity, as well as contextual factors, such as teaching load, class size, class format, availability of teaching assistant support, and consistency of policies and procedures, in supporting or hindering academic integrity. We also situated these results within a micro (individual), meso (departmental), macro (institutional), and mega (community) framework. Results from this study contribute to the growing body of empirical evidence about faculty perspectives on academic integrity in Canadian higher education and can inform the continued development of existing academic integrity supports at universities.